ASSOCIATION BETWEEN PESARIUM INSTALLATION AND VULVOVAGINAL CANDIDIASIS INCIDENT - Nur Hidayati; Eighty Mardiyan Kurniawati; Juniastuti Juniastuti (Universitas Airlangga, 2021)
Abstract Background: Vulvovaginal candidiasis (VVC) is one of the lower female genital tract infections caused by Candida sp. The Symptoms of VVC are more production of yellowish-white secretions, irritation, odor, itching in the genitals to swelling. One of the risk factors triggering CVV is the use pessaries in patients with uterine prolapse. This study aims to determine the relationship between pessary installation and Vulvovaginal Candidiasis (VVC) incident. Methods: this research uses a cross sectional study with a sampling technique that is purposive sampling. The sample used was POP patients with pessaries who visited Dr. Hospital. Soetomo in 2018 as many as 68 patients. The primary data in this study is a research form that has been prepared by the researcher, while the secondary data is patient medical records. Data analysis used the Chi-Square test with a Prevalence Ratio (PR) of 95% CI. Results: This study showed that the incidence of CVV was most commonly found in women aged >45 years with most of them being in primary education, using a pessary for more than 3 months and being a housewife, meanwhile the incidence of CVV was more common in POP women with pessaries than without a pessary. The results of the Chi-Square test showed that have a significant relationship between pessarium installation and the incidence of CVV (p=0.041). Conclusion: there is a relationship between pessary installation in POP patient and vulvovaginal candidiasis incident.